Trifluoro-icaritin alleviates mechanical hypersensitivity and improves motor coordination and balance in rats with spared nerve injury-induced neuropathic pain. (14th September 2021) - Jia, Dandan; Sun, Yalan; Liu, Guangsen; Xue, Meng; Huang, Zhihua; Huang, Cheng
Highlights: ICTF successfully ameliorates SNI-induced mechanical hypersensitivity. ICTF improves the motor coordination and balance in SNI rats. ICTF may be exploited as a potential candidate in the treatment of neuropathic pain. Abstract: Neuropathic pain is still one of the unsolved public health problems worldwide. Although the current reagents can attenuate neuropathic pain to a certain extent, their clinical application is very limited owing to larger toxicity and serious side effects. Trifluoro-icaritin (ICTF) has been documented to possess profound anti-inflammatory and neuroprotective activities, but whether ICTF exerts an anti-nociceptive effect on neuropathic pain remains unknown. Here, a rat model of spared nerve injury (SNI)-induced neuropathic pain was used. SNI rats were administrated with ICTF (i.p.) once daily lasting for 21 days, and subsequently the pain-related behaviors were evaluated by applying mechanical or thermal pain threshold, CatWalk gait parameter, and rotarod test on day 1 before and day 1, 3, 7, 10, 14, and 21 after SNI surgery, respectively. The results showed that ICTF (0.5 mg/kg, 1.5 mg/kg, and 5.0 mg/kg, i.p.) treatment alleviated SNI-induced mechanical allodynia but not thermal hyperalgesia in a dose-dependent manner. After administration of ICTF at the most effective dose of 5.0 mg/kg to SNI rats, CatWalk gait analysis revealed that ICTF not only significantly enhanced gait parameters including max contact max intensity, max intensity, print area, and stand time but also decreased the swing time; Rotarod test further exhibited that ICTF could effectively prolong the time on rod and increase the rotating speed in SNI rats. Additionally, following ICTF (5.0 mg/kg) treatment of SNI rats for 21 consecutive days, the max contact max intensity was found to be positively correlated with the rotating speed. Taken together, ICTF successfully ameliorates mechanical hypersensitivity and improves the motor coordination and balance in SNI rats, suggesting that ICTF may be exploited as a potential candidate in the management of neuropathic pain.